Synthetic strategies to incorporate Ru-terpyridyl water oxidation catalysts into MOFs: direct synthesis vs. post-synthetic approach. Issue 39 (30th September 2020) - Liseev, Timofey; Howe, Andrew; Hoque, Md Asmaul; Gimbert-Suriñach, Carolina; Llobet, Antoni; Ott, Sascha
Abstract : Incorporating molecular catalysts into metal–organic frameworks (MOFs) is a promising strategy for improving their catalytic longevity and recyclability. Abstract : Incorporating molecular catalysts into metal–organic frameworks (MOFs) is a promising strategy for improving their catalytic longevity and recyclability. In this article, we investigate and compare synthetic routes for the incorporation of the potent water oxidation catalyst Ru(tda)(pyCO2 H)2 (tda = 2, 2′:6′, 2′′-terpyridine-6, 6′′-dicarboxylic acid, pyCO2 H = iso-nicotinic acid) as a structural linker into a Zr-based UiO-type MOF. The task is challenging with this particular metallo-linker because of the equatorial dangling carboxylates that can potentially compete for Zr-coordination, as well as free rotation of the pyCO2 H groups around the HO2 Cpy⋯Ru⋯pyCO2 H axis. As a consequence, all attempts to synthesize a MOF with the metallo-linker directly under solvothermal conditions led to amorphous materials with the Ru(tda)(pyCO2 H)2 linker coordinating to the Zr nodes in ill-defined ways, resulting in multiple waves in the cyclic voltammograms of the solvothermally obtained materials. On the other hand, an indirect post-synthetic approach in which the Ru(tda)(pyCO2 H)2 linker is introduced into a preformed edba-MOF (edba = ethyne dibenzoic acid) of UiO topology results in the formation of the desired material. Interestingly, two distinctly different morphologies of the parent edba-MOF have been discovered, and the impact that the morphological difference has on linker incorporation is investigated.